100k views
2 votes
Solve the following system using substitution.

Solve the following system using substitution.-example-1

1 Answer

5 votes

Answer/Step-by-step explanation:

3. By substitution method, let's substitute
(2)/(3)x- 4 for y in the first equation.

Thus,


(1)/(3)x + 2((2)/(3)x- 4) = 1

Solve for x


(x)/(3) + (4x)/(3) - 4 = 1

Add 4 to both sides


(x)/(3) + (4x)/(3) - 4 + 4 = 1 + 4


(x)/(3) + (4x)/(3) = 5


(x + 4x)/(3) = 5


(5x)/(3) = 5

Multiply both sides by 3


(5x)/(3)*3 = 5*3


5x = 15

Divide both sides by 5


x = 3

Now, substitute 3 for x in the equation.


y = (2)/(3)x- 4


y = (2)/(3)(3) - 4


y = 2 - 4


y = -2

The solution of the equation is x = 3, y = -2

4. Solving by elimination, let's try to eliminate the x-variable by adding both equation together.


3x - 2y = 11


-3x - y = 4


-3y = 15 =>
(-3x +(-3x) = 0; -2y +(-y) = -3y; 11 + 4 = 15)

Divide both sides by -3 to solve for y


(-3y)/(-3) = (15)/(-3)


y = -5

Substitute -5 for y in the first equation to find x


3x - 2(-5) = 11


3x + 10 = 11

Subtract 10 from both sides


3x + 10 - 10 = 11 - 10


3x = 1

Divide both sides by 3


(3x)/(3) = (1)/(3)


x = (1)/(3)

The solution is
x = (1)/(3), y = -5

User Ryan Lavelle
by
5.4k points